Investigating the effect of dyeing on the surface of wool fibres with atomic force microscopy (AFM) - Abduallah, Abduelmaged (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.